Venous Thromboembolism in Patients With Myeloma: Incidence and Risk Factors in a "Real-World" Population. (September 2014) - Crowley, Maeve P.; Eustace, Joseph A.; O'Shea, Susan I.; Gilligan, Oonagh M.
Myeloma has a well-described association with venous thromboembolism (VTE). There are few dedicated studies investigating the incidence and risk factors. Many assessment scores have been suggested to estimate the risk of VTE in patients with cancer but these have been validated in solid organ tumors. The records of patients with myeloma attending a university hospital between January 2007 and December 2012 were reviewed to investigate the incidence of VTE and the associated risk factors. In all, 217 patients with a mean (standard deviation) age at diagnosis of 65 (12) years were included. Of 217 patients, 12% had an episode of VTE, 69% received at least 1 immunomodulatory agent, and 95% had low or intermediate risk of VTE according to the Khorana score. Venous thromboembolism was a frequent occurrence in this cohort. Patients had many risk factors for VTE but no one was predictive. As myeloma outcomes continue to improve, a dedicated prospective study is warranted to investigate the most appropriate thromboprophylaxis strategy.